Experimental parasite community ecology: intraspecific variation in a large tapeworm affects community assembly. (12th May 2016) - Benesh, Daniel P.; Kalbe, Martin
Abstract : Hosts often harbour multiple parasite species, some of which may co‐occur more or less frequently than expected by chance. Using a combination of laboratory and field experiments, the authors found that the non‐random associations between parasite species can be contingent on variation within a species. Summary: Non‐random species associations occur in naturally sampled parasite communities. The processes resulting in predictable community structure (e.g. particular host behaviours, cross‐immunity, interspecific competition) could be affected by traits that vary within a parasite species, like growth or antigenicity. We experimentally infected three‐spined sticklebacks with a large tapeworm ( Schistocephalus solidus ) that impacts the energy needs, foraging behaviour and immune reactions of its host. The tapeworms came from two populations, characterized by high or low growth in sticklebacks. Our goal was to evaluate how this parasite, and variation in its growth, affects the acquisition of other parasites. Fish infected with S. solidus were placed into cages in a lake to expose them to the natural parasite community. We also performed a laboratory experiment in which infected fish were exposed to a fixed dose of a common trematode parasite. In the field experiment, infection with S. solidus affected the abundance of four parasite species, relative to controls. For two of the four species, changes occurred only in fish harbouring the high‐growth S. solidus ; one species increased in abundance and the other decreased. These changes did not appear to be directly linked to S. solidus growth though. The parasite exhibiting elevated abundance was the same trematode used in the laboratory infection. In that experiment, we found a similar infection pattern, suggesting that S. solidus affects the physiological susceptibility of fish to this trematode. Associations between S. solidus and other parasites occur and vary in direction. However, some of these associations were contingent on the S. solidus population, suggesting that intraspecific variability can affect the assembly of parasite communities.